Mistreatment or not the best treatment to the elder. Reality and challenge - Miguel Angel Serra Valdés; Girelda Cordero López; Marleny Viera García (Medisur)
There is inconsistency in the definition and understanding of abuse to the elder. An appropriate and unified definition is presented by the World Health Organization. It states that elder abuse is any isolated or repeated act, or the absence of appropriate action, that occurs in any relation from which confidence and safety is expected and produces damage or general discomfort. Mistreatment and the not best treatment to these people is a problem to be solved worldwide. In this article issues related to the topic are approached, some types of mistreatment, causes identified in studies carried out so as strategies and actions to fight them. These aspects are presented not only for the health system but for the society as well. Cuba is not exempted of this situation; the Cuban population ages and chronic non communicable diseases are a challenge to be concerned, mainly cancer, dementia, disability and prostration due to different causes which are the most frequent illnesses in elder people.